Associated factors of the co-occurrence of trachoma and soil-transmitted helminthiases in children 1 to 9 years old in rural communities of the Amazon basin in Loreto Department, Peru: Results from a population-based survey - Martha Idalí Saboyá-Díaz; Cristiam Armando Carey Angeles; Rosario del Socorro Avellaneda Yajahuanca; Salvith Karen Meléndez Ruíz; Rufino Cabrera; Harvy Alberto Honorio Morales; Paul E. Pachas; Monica Guardo; Kristen K. Renneker; Beatriz E. Muñoz; Sheila K. West (Public Library of Science (PLoS), 2022)
Background There is evidence of the occurrence of trachoma in Peru, and studies have shown that soil-transmitted helminthiases (STH) are affecting rural communities in the Amazon basin in Loreto Department. This study was done to estimate trachoma prevalence, STH prevalence, and the associated factors for both diseases in children aged 1-9 years in rural communities of Peru. Methodology A population-based cross-sectional survey was carried out in rural communities of Loreto. A standardized survey questionnaire with individual and household risk factors related to both diseases was used. Ocular examination was done for all participants aged one year and above, and eye swab samples were collected from children with follicular trachoma (TF). Anthropometric measurements, stool samples for STH, and blood samples for hemoglobin measurement were taken from children. Principal findings TF prevalence was 7.74% (95% CI 5.08-11.63%), STH prevalence was 49.49% (95% CI 25.00-52.43%), and prevalence of co-occurrence of both diseases was 5.06% (95% CI 2.80-8.98%) in children aged 1-9 years. Being at age 3-8 years old (AOR = 6.76; 95% CI 1.346-33.947), have an unclean face (AOR = 24.64; 95% CI 6.787-89.444), and having been dewormed in the last six months (AOR = 2.47; 95% CI 1.106-5.514), were risk factors of TF. Being a female (AOR = 0.22; 95% CI 0.103-0.457) was associated with decreased odds of TF. Having been dewormed in the last six months (AOR = 0.30; 95% CI 0.139-0.628) was a preventative factor for STH. Risk factors for children with both diseases mirrored the findings for risk factors for individual diseases. Conclusions Neglected tropical diseases and associated risk factors overlap in communities living in vulnerable conditions in the Amazon basin of Peru. These findings support the need to implement integrated interventions, including mass drug administration, water, sanitation, and hygiene for both diseases in the study area. Author summary Trachoma is an infectious disease caused by the bacterium Chlamydia trachomatis, transmitted through person-to-person contact, and it is the world's leading infectious cause of blindness. Soil-transmitted helminths (STH) is a group of intestinal parasites composed of Ascaris lumbricoides (roundworms), Trichuris trichiura (whipworms), and Ancylostoma duodenale and Necator Americanus (hookworms), that are transmitted by fecal contamination of the soil and adversely affect nutritional status and impair cognitive processes in children. Although there is evidence of the occurrence of trachoma in several areas of Peru, an epidemiological study has not been carried out to determine if it is a public health problem. STH infections have been reported to affect children in areas of the Loreto Department in Peru, but prevalence surveys in rural communities bordering Brazil and Colombia have not been carried out. In this study, we present the results of an integrated survey for trachoma and STH in Loreto and the factors associated with the occurrence of these diseases. The results of this study show that both diseases and risk factors overlap, supporting the need to implement integrated interventions to eliminate them as public health problems in communities living in vulnerable conditions in the Amazon basin of Peru.